Prognostic Value of Lactate and Central Venous Oxygen Saturation after Early Resuscitation in Sepsis Patients - Lee, Young Kun (PLoS One, 2016)
The objective of this study was to evaluate the prognostic value of static and dynamic variables of central venous oxygen saturation (ScvO(2)) and lactate in patients with severe sepsis or septic shock who underwent early quantitative resuscitation. We also investigated whether ScvO(2) measured after initial resuscitation could provide additive prognostic value to that of lactate. We analyzed the sepsis registry for patients presenting to the emergency department and included patients with simultaneous measurements of lactate and ScvO(2) at the time of presentation (H0) and 6 hours (H6) after resuscitation. The primary outcome was 28-day mortality and multivariable logistic analysis was used to adjust for confounders. A total of 363 patients were included, and the overall 28-day mortality was 18%. The area under the receiver operator characteristic curve for predicting 28-day mortality was as follows: lactate (H6), 0.81; lactate (H0), 0.73; relative lactate change, 0.67; ScvO(2) (H6), 0.65; relative ScvO(2) change 0.59; ScvO(2) (H0), 0.58. Patients with lactate normalization showed significantly lower 28-day mortality compared to patients without lactate normalization (3% vs. 28%, P<0.01). However, in those who achieved ScvO(2) (H6) ≥70%, there was a significant difference in 28-mortality only in patients without lactate normalization (21% vs. 39%, P<0.01) but no difference in those with lactate normalization (4% vs. 3%, P = 0.71). In multivariable analysis, lactate normalization was significantly associated with 28-day mortality (adjusted odds ratio [OR] for 28-day mortality, 0.20; 95% confidence interval [CI], 0.07–0.54; P <0.01), but ScvO(2) (H6) ≥70% showed only a marginal association (the adjusted OR for 28-day mortality, 0.51; 95% CI, 0.26–1.01; P = 0.05). ScvO(2) (H6) ≥70% was associated with 28-day mortality only in cases without lactate normalization in subgroup analysis (adjusted OR 0.37, 95% CI, 0.18–0.79; P = 0.01). Six-hour lactate was the strongest predictor of 28-day mortality in patients with severe sepsis or septic shock. Six-hour ScvO(2) provided additional prognostic value only in cases where lactate values were not normalized after resuscitation.